In silico assessment of Nandhi Mezhugu as a potential therapeutic agent against Diethylnitrosamine (DEN) – induced Hepatocellular Carcinoma; Molecular Docking insights - Indumathi. R; Ganne Venkata Sudhakar Rao; Pazhanivel. N; Srinivasan. M.R.; Jalantha. P; Sowmya . M (The Indian Veterinary Journal, 2025)
Hepatocellular carcinoma is the most common liver tumour in dogs. It is the sixth most common cancer in the world in humans and ranks third in causing cancer related mortality. Diethyl nitrosamine (DEN) is a potent liver carcinogen which is ideal for induction of liver cancer in experimental carcinogenesis. Caspase – 3, Bax , BCl2, NF-ĸB are few of the many tumour markers which are useful in diagnosis of cancer. Nandhi Mezhugu is a Siddha - herbo mineral formulation that has been scientifically validated is being used for rheumatism, skin diseases and various types of cancers. The active principles in Nandhi Mezhugu namely Withaferin-A , Brucine, Piperine, were selected and their structures were retrieved. Molecular docking was performed against 5 tumour marker proteins, Caspase – 3, Bax, , BCl2, NF-ĸB. The results showed that Withaferin- A had the most favourable binding affinity, followed by Brucine, Piperine . The results of this study indicated a profound insilico interaction between the active principles present in Nandhi Mezhugu and the tumour markers.